PENGARUH KEBIJAKAN SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) TERHADAP TINGKAT KEPUASAN PESERTA DIDIK DI SEKOLAH MENENGAH ATAS (SMA) NEGERI 1 MAJENANG - , Sabrina Putri Ratna Dewi; Tri Asih Wismaningtyas; Yuni Kurniasih (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The zoning system policy is a government policy on yhe implementation of PPDB which is based on the radius of the educational unit zone with the student’s place of residence which aims to provide students with equal opportunities to recive quality educational services and eliminate discrimination. However, in implementing the zoning system policy there are still several problems. This can be seen in the PPDB by implementing the zoning system policy at Majenang 1st State High School which still found several problems, including the discovery of data manipulation by prospective new students. Apart from that, there are still cases of domicile migration. The purpose of this study is to determine how much influence the zoning system policy has on the level of student satisfaction at Majenang 1st State High School . This research uses a quantitative approach with a survey research method. The population in this study was all students at Majenang 1st State High School, totaling around 1.140 students. The sample selection technique used was proportionate stratified random sampling with calculations using the Slovin formula, the result of which was 100 respondents. This study shows that there is a strong and positive relationship between the zoning system policy variable and the satisfaction level variable, where the zoning system policy has an effect of 47.3% on the satisfaction level variable.